Stab Wounds to The Chest that Penetrated The Heart - Hendri Meirialdi Saputra; Abdul Gafar Perinduri (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Sharp trauma is an abnormality in the body caused by the contact of objects whose surface is able to slice so that tissue continuity disappears. It is usually caused by knives, swords, scissors, razors, axes and others. The types of wounds due to sharp violence that can be identified are stab wounds, iris wounds and also stab wounds. All of these types of injuries can endanger the victim's life and cause death for the victim. Every case of persecution or violence against life that causes death must be medically examined. This must be done to help the police as law enforcers in uncovering murder cases based on forensic medical science. This examination includes an examination of the outside of the victim's body and also an examination of the victim's internal organs. The results will be used as valid evidence used in the judicial process. Case description: A case was reported, a male corpse, known, with the initials DR, with the suspected death of elements of a criminal act.Conclusion From the results of the examination, the cause of death of the victim was a stab wound to the left chest that penetrated the heart and heart sac due to sharp violence that resulted in bleeding and tissue damage..